PENERAPAN KONSEP FUNGSI LINEAR DALAM EKONOMI DAN BISNIS: Application of Linear Function Concept in Economics and Business - Nugraha, Yuda Satria (Yayasan Al-Amin Qalbu, 2024)
This research aims to determine the application of linear function concept in economics and business. A linear function is the simplest function because it only has one independent variable and has a power of one. This research is qualitative research that uses a literature study method with an exploratory approach. Data collection techniques are carried out by collecting valid secondary data sources from books, scientific journals and the internet. The research results show several linear function models, namely the demand function Qdx = -a.Pdx +b , the supply function Qsx = a.Psx +b , the market balance point from the linear equation Pdx = Psx , the consumption function C = C0 + cY , the savings function S = C0 + (1 - c ) Y, and the production cost function TC = TFC + TVC.